Assessment of drilling-induced delamination and tool wear in carbon fibre reinforced laminates. Issue 9 (November 2021) - Arhamnamazi, SA; Aymerich, F; Buonadonna, P; Mehtedi, M El
A highly accurate X-ray damage characterization technique was used in this study to investigate the correlation between hole damage, tool wear and thrust force in drilling of carbon fibre reinforced laminates. Woven carbon/epoxy panels were drilled with a twist tool for 592 holes and the internal damage induced by drilling was investigated by high-resolution penetrant-enhanced X-radiography for comparison with damage evaluated by visual inspection. The study shows that the dominant damage mode induced by drilling is delamination and that tool wear has a significant effect on the size of the delaminated area. The analyses also show that the delaminated areas estimated by visual inspection are much smaller than those identified by X-radiography. This finding indicates that visual observation techniques may provide dangerously unconservative indications and should be used in association with more reliable damage evaluation methods to assess the hole quality of drilled carbon fibre reinforced composites.